PRAKTIKUM FISIKA SEBAGAI BAGIAN BUDIDAYA UNGGUL - Aprijanto (Journal Sains dan Teknologi Budidaya Perairan (SINTASAN), 2024)
The scientific use of physical principles can enable aquaculture experts to create a comfortable environment for farmed marine animals to grow and develop well. This research uses a qualitative method with a case study approach that combines analysis of human actions. Eleven respondents participated in the physics practicum, mainly students from the fisheries and marine sciences faculty at Pancasakti University, Tegal. The results show that the connection with knowledge of physics comes from the hobby of studying at high school or vocational high school, and some students consider the important role of practicum as the forerunner of knowledge. The evident from the suitability of the interests of the school environment, which is important in practicums and physics courses.